(untitled) (Academicia Globe: Inderscience Research, 2022)
This paper aims to assess and know the role of intravenous analgesic agents in patients on mechanical ventilation A survey was conducted in Baghdad Hospital, where 150 patients were collected, divided into two groups, and the average age ranged between forty to 60 years.The questionnaire questions were also relied upon in addition to the information in the electronic record in the hospital, and all statistical data was analyzed by the reliance on the program. IBM SPSS soft 25 and MS excel The process of treating patients in life-threatening situations in the intensive care unit (ICU) does not exclude the conduct of diagnostic and treatment procedures outside The role of intravenous analgesics in anaesthesia has always been fundamental to practical anaesthesia. Their inclusion as a specific component of balanced anaesthesia is widely accepted and has certain advantages. Use of intravenous analgesics during induction of anaesthesia, induction becomes smoother, drugs required to stop consciousness decrease, and the cardiovascular response to laryngoscopy and endotracheal intubation is reduced.